Virtual solar system project: Building understanding through model building - Barab, Sasha; Hay, Kenneth E.; Barnett, Michael; Keating, Thomas (Journal of Research in Science Teaching, 2000)
In this manuscript we describe our introductory astronomy course for undergraduate students in which students use three-dimensional (3-D) modeling tools to model the solar system and, in the process, develop rich understandings of astronomical phenomena. Consistent with our participatory pedagogical framework, it was our intention to establish a context that supported students in carrying out scientific inquiry using virtual models they developed. The progression of our thinking and the course curriculum has been grounded in a series of
Keywords: TIC; apprentissage par projet; ressources pédagogiques; sciences